Experimental model to describe the dielectric response of different dye and nanoparticles doped hydrogels for biological cell membranes and biological systems - Coskun, R.; Okutan, M.; Ozturk, M.; Yalcin, O. (ELSEVIER, 2019)
Doped hydrogels with Methylene-Blue (MB), Rhodamine-B (RB), MB/RB dyes and NiFe2O4 nanoparticles (NPs) were developed as an experimental model to describe the dielectric/electric response of lipid matrix in biological cell membranes and biological systems. Hydrogels synthesized by polymerization technique are highly suitable for three-dimensional cell models due to biocompatible structure. Frequency and bias voltage evolution of dielectric and electrical parameters for all samples have been characterized by the impedance spectroscopy at room temperature (RT). Absorbance spectrum and energy band gap for all samples have been analyzed with UV-Vis absorption spectroscopy. The frequency and applied bias voltage dependence of experimental dielectric/electric properties for all samples were attributed to the basis of Kroop's theory, Maxwell-Wagner approach, viscoelastic mechanism and the micro Brownian motion of free ions. It was obtained that the absorbance spectrum values for all samples are associated with Lambert-Beer-Bouguer's law and innervation of the dipolar oscillations/quadrupoles of dye and NPs ions. The smallest and highest values of the absorption spectra were recorded for MB/RB dye and NiFe2O4 NPs doped hydrogels with respectively. Results from the complex impedance based Cole-Cole plots and their Smith Chart adaptation showed that MB/RB dye doped hydrogels has the largest semi-circle due to it has the highest relaxation times and the smallest absorption coefficient. The NiFe2O4 NPs doped hydrogels with the highest absorption value were found to be the most suitable samples for optoelectronic applications in the biological cell membranes. The MB/RB dye doped hydrogels were concluded to be the most suitable material for impedance applications due to have the greatest relaxation time in the Cole-Cole plots. It determined that all of all samples except RB doped hydrogels are exhibited Ohmic behaviour from the I-V characteristic analysis. The conductivity properties (from the power law exponent) in 1th region, the 2nd region and the 3rd region for dyes/NiFe2O4 NPs doped hydrogels were associated with the dc conductivity, the Correlated Barrier Hoping (CBH)/Quantum Mechanical Tunnel (QMT) conductivity and the Correlated Barrier Hoping model with respectively. It is concluded that RB dye doped hydrogels can be used as a model for biomedical devices and drug delivery system applications, because they have the highest dielectric and superior conductivity properties. Also, different cationic dyes and NiFe2O4 NPs doped hydrogels were found exciting in applications such as low-cost bio-flexible sensors, green electronics and health monitors that have in low-voltage-operating. (C) 2019 Published by Elsevier B.V.
Keywords: Hydrogels; Dielectric; Conductivity; Nanoparticles; Biological system; CURRENT-VOLTAGE CHARACTERISTICS; ELECTRIC MODULUS; BROWNIAN-MOTION; GOLD NANOPARTICLES; SYNTHETIC CIRCUITS; OPTICAL-PROPERTIES; POLYMER; IMPEDANCE; FREQUENCY; Chemistry; Physics